Additional desmids (Chlorophyceae) to eastern flora of Nepal - Rai, Shiva Kumar (Nepalese Journal of Biosciences, 2014)
Desmid of eastern Nepal has been studied. A total 15 desmids are described from different freshwater lotic and lentic habitats in the present communication. They belong to genera Closterium (8), Pleurotaenium (2), Cylindrocystis (1), Micrasterias (1), Arthrodesmus (1), Staurastrum (1) and Spondylosium (1). These are the addition of desmids from different locality to the algal flora of eastern Nepal.